JOB SATISFACTION AS AN INTERVENER: WORKLOAD, BURNOUT, AND HOTEL EMPLOYEE PERFORMANCE - Zahro, Siti Fatimatuz; Ayu, Pitaloka Dharma; Nurmiyati, Nurmiyati (Universitas Muhammadiyah Tangerang, 2025)
High work demands and emotional pressure in the hospitality industry have the potential to reduce employee performance. This study aims to analyze the influence of workload and burnout on employee performance, with job satisfaction as an intervening variable. Using a quantitative approach, data was collected through a survey of 86 employees of The Wujil Resort & Conventions Hotel. The analysis was carried out using the structural equation modeling (SEM) method using SmartPLS 4.0. The results show that workload and burnout have a significant effect on performance and job satisfaction. Additionally, job satisfaction has been shown to mediate the relationship between workload, burnout, and employee performance. These findings underscore the importance of workload management and burnout prevention to improve employee satisfaction and performance. The novelty of the research lies in the integration of job satisfaction as an intervening variable in the context of the hospitality industry, which is still rarely studied empirically. His practical contributions provide a foundation for hotel management in designing healthier and more productive work strategies.